COMPARATIVE SELECTIVITY AND CATCHABILTY OF POT AND TUBE FOR CONGER EEL (Conger Myriaster) - Dahri Iskandar (JOURNAL OF COASTAL DEVELOPMENT, 2011)
The objective of this experiment was to develop a method to estimate mesh selectivity of pot and comparative catchability between pot and tube for white spotted conger eel (Conger Myriaster). About ten times comparative fishing experiments were carried out off Haneda in Tokyo Bay, during October and November every year from 1997 to 2000. The experiment used collapsible pots of 5 mesh openings (21.0, 18.1, 15.5, 13.6 and 11.6 mm) and tube of 9.06 mm hole diameter as control gear. Result of this experiment indicated that pot of larger mesh size caught larger conger. Significant different was found in length distributions between the four years (ANOVA Test, P=1.9x10-45) and then the data were not combined for the analysis. In term of girth-perimeter ratio, R value of 50% retention and selection range were calculated to be 1.19 and 0.24 from estimated logistic parameters, (α,β)=(-10.67, 8.99). When catchability of tube was assumed to be 1, relative catchability of pot with 21.0, 18.1, 15.5, 13.6 and 11.6 mm mesh openings were 0.62, 0.79, 0.73, 0.63 and 0.51, respectively. This suggested that one tube could catch more conger eel than one pot and pot of larger mesh size was likely to catch of larger size more effectively.